PERAN PRAKTISI HUBUNGAN MASYARAKAT DI TENGAH PERKEMBANGAN KECERDASAN BUATAN - Hamzah Ramadhan (Acta Diurna: Jurnal Ilmu Komunikasi, 2025)
The study delves into the adoption of Artificial Intelligence (AI) in the field of public relations (PR) among professionals in Indonesia. This exploration is based on in-depth interviews with 8 individuals and a survey completed by 100 PR practitioners with a minimum of two years of experience. The study results indicate widespread utilization of tools such as ChatGPT, Bard, Grammarly, and Canva for tasks such as research, planning, and content personalization. These AI tools have been instrumental in improving operational efficiency by aiding in information management. Nevertheless, there are apprehensions regarding the potential dissemination of misleading or controversial content due to imperfections in AI-generated material, which could adversely impact an organization's credibility. Consequently, it is imperative to exercise human oversight to validate the accuracy and appropriateness of content produced by AI tools. Furthermore, concerns have been raised about a potential decline in the demand for PR practitioners as these advanced AI tools are adept at generating content that closely resembles human-created material. This presents a challenge for professionals to uphold their relevance within the industry. However, despite these concerns, the prevailing sentiment is that the evolving technological landscape offers opportunities for professional development. By actively engaging in workshops and staying abreast of technological advancements, PR practitioners may effectively harness these tools to enrich their work and stay competitive in their field. Embracing AI presents prospects for skill enhancement and innovative approaches within the PR domain, ensuring practitioners can continue providing value in an ever-changing environment.